The Criteria of Good English Textbook for Students: A Senior English Textbook Analysis - Akhmad, Enni; R. Saleh, Yuwin; Pakaya, Susanti (Language Development Center, 2022)
Background: United Kingdom textbooks are a medium for delivering material, good material must be supported by good textbooks in accordance with the 8 ideal criteria of textbooks. Purpose: This study aims to analyze and describe the United Kingdom textbooks used in SMA Negeri 1 Gorontalo Regency Method: This study uses a qualitative method with an approach to analyzing the content of textbooks. Data was obtained through an observation system on topics, language aspects, task forms for 4 language skills, and task structure in each chapter of the book. The textbook analyzed is a textbook for high school students in grade X published by the Ministry of Education and Culture in the K-13 curriculum edition in 2017 Results and Discussion: The results of the study show that of the 8 criteria for a good textbook, this book meets the 5 criteria set. The 5 criteria are having clear goals and approaches, book design and organization, language content, language skills, language topics and practice situations Conclusions and Implications: This study concludes that this book is worthy of being recommended to be used as a textbook for students. This research has implications for efforts to improve students' mastery of United Kingdom language skills through the teaching materials in the textbooks used